TEM characterization on new 9% Cr advanced steels thermomechanical treated after tempering - Fernández, P.; Hoffmann, J.; Rieth, M.; Roldán, Marcelo; Gómez Herrero, A. (My University, 2018)
Phase transformation on new six reduced activation ferritic/martensitic steels (RAFMs) was investigated to provide the basis for the design and development of advanced steels to maintain adequate strength and creep resistance above 500¿°C. The new alloys are designed to increase the amount of fine MX precipitates and reduce coarse M23C6 carbides through alloy composition refinement and the application of thermomechanical treatments. The microstructural investigations by TEM have shown M23C6, M2X, and MX precipitation after tempering at 700¿°C/2h with low dislocation recovery, while at 825¿°C/2h the martensite developed to subgrain formation and growth. At this stage, only M23C6 and MX were detected. Preliminary results demonstrate that it is feasible to produce fine MX strengthened particles dispersed in the matrix with further optimization of tempering treatments.